Simulation of Three Dimensional Liquid-Sloshing Models using C++ Open Source Code CFD Software - Chaichanasiri , Ekachai; Suvanjumrat, Chakrit (Agriculture and Natural Resources, 2012)
The open source computational ﬂ uid dynamic (CFD) codes—open ﬁ eld operation and manipulation (OpenFOAM)—were developed to simulate the three dimensional sloshing of liquid inside moving rectangular tanks. Equations governing the two-phases of ﬂ uid were used in these simulations and the Volume of Fluid method was used to capture the free surface of the liquid sloshing. The ﬁ nite volume method was used to solve these problems. The solutions of the simulations were validated using experiment results based on the free surface height and the pressure developed on the wall of the tanks. It was found that the average error of the surface height and the pressure obtained from the simulations were 2.33% and 6.65%, respectively.